A Highly Efficient Luminescent Metal–Organic Framework with Strong Conjugate Unit for Sensing Small Molecules - Chai, Bi‐Lian; Xu, Hui; Zheng, Teng‐Fei; Chen, Jing‐Lin; Liu, Sui‐Jun; Yu, Mei‐Hui; Wen, He‐Rui (Chinese journal of chemistry, 2022)
Comprehensive Summary Luminescent metal–organic frameworks (LMOFs) have become a promising class of fluorescence sensing materials, however, the multi‐responsive LMOF sensors for organic compounds are rather rare. Herein, a water stable and highly efficient luminescent MOF with the formula of {[Zn(BBZB)(2,6‐NDC)]·solvents}n (JXUST‐10, BBZB = 4,7‐bis(1H‐benzimidazole‐1‐yl)‐2,1,3‐benzothiadiazole and 2,6‐NDC = 2,6‐naphthalenedicarboxylate) was constructed by the incorporation of Zn2+ and two organic ligands (BBZB and 2,6‐NDC) featuring the conjugate system. JXUST‐10 is a three‐dimensional two‐fold interpenetrated framework with good fluorescent property. Based on the luminescent characteristic, JXUST‐10 can be used as a multi‐responsive sensor for detection of three different analytes including tetracycline, benzaldehyde and uric acid via different luminescent change behaviours. Remarkably, fluorescence test paper and LED light devices are used to detect analytes through the visual change of luminescence colour of JXUST‐10 from blue greenish to yellow greenish under ultraviolet light (365 nm) irradiation. Furthermore, the probable sensing mechanisms for three target analytes were also discussed. A water stable and highly efficient luminescence MOF (JXUST‐10) can simply sense tetracycline, benzaldehyde and uric acid via different fluorescence behaviour. Remarkably, fluorescence test paper and LED light devices are applied to detect benzaldehyde and uric acid through the visual change of luminescence color of JXUST‐10.